PENINGKATAN MUTU PEMERIKSAAN DI LABORATORIUM KLINIK RUMAH SAKIT - Kahar, Hartono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2005)
Clinicians always needs the results of clinical laboratory with quality assurance. The performance of good quality laboratory depends on pre-analytic, analytic as well as post analytic processes. It is also influenced by reagents and methods types as well as personal laboratory work. The goal of laboratory examinations quality runs between QMS, or Five Q’s, which consist of: Quality planning, laboratory practice, control, and assurance and Quality improvement. The quality laboratory examinations depend on the accuracy and precision results.